2015
DOI: 10.1073/pnas.1412277112
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid origins and the earliest stages of diploidization in the highly successful recent polyploid Capsella bursa-pastoris

Abstract: Whole-genome duplication (WGD) events have occurred repeatedly during flowering plant evolution, and there is growing evidence for predictable patterns of gene retention and loss following polyploidization. Despite these important insights, the rate and processes governing the earliest stages of diploidization remain poorly understood, and the relative importance of genetic drift, positive selection, and relaxed purifying selection in the process of gene degeneration and loss is unclear. Here, we conduct whole… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
138
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 142 publications
(152 citation statements)
references
References 48 publications
14
138
0
Order By: Relevance
“…Complete genome sequencing of the different birch species that could have been involved in this polyploidization event is needed to confirm this result. The ongoing sequencing, assembly and annotation of the B. pendula genome together with recent advances in phasing methods of tetraploid genomes (Douglas et al 2015) suggest that we will soon have the answer. Y.T., G.G.V.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Complete genome sequencing of the different birch species that could have been involved in this polyploidization event is needed to confirm this result. The ongoing sequencing, assembly and annotation of the B. pendula genome together with recent advances in phasing methods of tetraploid genomes (Douglas et al 2015) suggest that we will soon have the answer. Y.T., G.G.V.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, birch species have different ploidy levels, and B. pendula, B. platyphylla, B. nana and B. maximowicziana are diploids (2n = 2x = 28), while B. pubescens and B. ermanii are tetraploids (2n = 4x = 56), offering the possibility to assess the advantages conferred by polyploidy through past recolonization episodes. Although polyploidization plays an important role in plant speciation (Stebbins 1971;Grant 1981;Coyne & Orr 2004;St Onge et al 2012;Douglas et al 2015), the process of polyploidization (autoploidy or alloploidy) of birch species has not been examined using molecular markers. Nuclear DNA markers can provide the high resolution required to evaluate the process of polyploidization, as recently demonstrated for example in Arabidopsis suecica (Jakobsson et al 2006) and Capsella bursa-pastoris (Douglas et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…To identify candidate causal mutations for the loss of SI in C. orientalis, we analyzed sequence alignments of the two key Slocus genes SRK and SCR, as well as the S-linked U-box gene, which may act as a modifier of the SI response . Specifically, we searched for major-effect variants resulting in frameshifts, premature stop codons or nonconsensus splice sites, present in sequences from the SC C. orientalis and/or in the SC C. bursa-pastoris B subgenome, which is derived from C. orientalis (Douglas et al, 2015), but not in sequences from the same haplogroup found in the SI species C. grandiflora and A. halleri. For SRK we identified nonsynonymous changes in hypervariable regions important for SRK specificity (Kusaba et al, 1997;Nishio & Kusaba, 2000), based on a protein sequence alignment of Capsella SRK with Brassica rapa SRK9, which represents a different haplogroup, but whose protein structure and interaction with SCR has been resolved recently (Ma et al, 2016).…”
Section: Candidate Mutations For the Loss Of Si In C Orientalismentioning
confidence: 99%
“…In Capsella, SI is the ancestral state, as there is trans-specific shared S-locus polymorphism between the outcrossing SI species Capsella grandiflora and outcrossing SI Arabidopsis species (Guo et al, 2009). Nevertheless, SC has evolved repeatedly in Capsella, resulting in two selfcompatible and highly selfing diploid species, Capsella rubella and Capsella orientalis, as well as the selfing allotetraploid Capsella bursa-pastoris, which formed by hybridization between C. orientalis and C. grandiflora accompanied by genome duplication (Douglas et al, 2015). These species also differ greatly in their geographical distributions, with C. bursa-pastoris having a nearly world-wide distribution, whereas C. rubella is mainly found in Central and Southern Europe, and C. orientalis has a distribution ranging from Eastern Europe to Central Asia (Hurka et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the two types of Oryza polyploids, we suggest that inconsistent evolutionary patterns of R in these polyploids are probably associated with different evolutionary time, asymmetrical subgenome evolutionary dynamics, and/or unique demographical characteristics of these species. Generally, most duplicated genes in polyploids were considered to have experienced a brief period of relaxed selection early in their history, with a moderate fraction evolving in an effectively neutral manner during this period; therefore, allopolyploids were usually characterized by relaxed purifying selection rather than rapid gene loss in their early stages of evolution (Lynch & Conery, 2000;Douglas et al, 2015). In contrast to Oryza CCDD species that originated ca.…”
Section: Discussionmentioning
confidence: 99%